Analys och konstruktion av kamerahus till backkamera - Olofsson, Britta (2011)
Revitrack, a business situated in Luleå, Sweden, has developed a rear view camera with a series ofspecial features to make reversing with caravans and large trailers safer. For this rear view cameraa housing has been developed. This housing has to be robust because the environment in which itwill be mounted is exposed to dirt, rain, snow, ice and stone chips from other vehicles that may harmit. Mounting and adjustment of the camera must be simple and intuitive. An important part of thedevelopment has been to make the camera plain and thereby not be attractive to thieves.A brief analysis of the rear view camera market and the attitude towards reversing aids has been made.A questionnaire was made for caravan owners and interviews with caravan sellers took place. Theresults from the questionnaire shows that reversing aids are a big help to the driver but at the presenttime they are too expensive for the owners to invest in them. The statistical population was limited sothe results has been seen as advisory rather than the statistically correct.The result of the project is a 3d-model printed with a rapid prototyping printer and 3D-modelsmade in NX4 which can be used as production plans. The printed model will be used by Revitrackat conventions and for business contacts to showcase the product and its appearance, function andstrengths. Validerat; 20110526 (anonymous)